Vasovagal presyncope response misdiagnosed as an allergic reaction to local anesthesia: A case report - Elsagali, Abeer Hussen; Elmezwghi, Abdurahman Musbah; Ashmmam, Musbah (Libyan Journal of Dentistry, 2018)
Presyncope is often defined as a temporary light-headed or dizzy feeling or a transitory reduction but not loss of consciousness. The presyncope vasovagal response can be triggered by stress, prolonged standing, extreme emotions, or severe pain, it occurs due to a reflex bradycardia and peripheral vasodilation (hypotension). A diagnosis of presyncope is often difficult to make, it can quite easily be confused with other conditions. Adverse reactions to local anesthetics (LAs) are widely reported. These include dose-related toxic effects, subjective psychomotor symptoms and true allergic reactions. Although local anesthesia (LA) are well-tolerated drugs, they precipitate adverse reactions. True allergic reaction represents only 1% of adverse reactions to local anesthetics (LAs).The diagnosis of unexpected adverse reactions during local anesthesia is a difficult issue. Nevertheless, Diagnosis may be confirmed with clinical presentation and skin test results. It is common for dental practitioners to misdiagnose a serious adverse event to LAs as an allergic reaction. The aim of this report is to determine knowledge of the dental practitioner about the proper history, symptoms, signs, investigations and how to differentiate between presyncope vasovagal reflex and allergic reaction of dental local anesthesia